GABA-enriched water dropwort produced by co-fermentation with Leuconostoc mesenteroides SM and Lactobacillus plantarum K154. (November 2016) - Kwon, Soon-Young; Garcia, Coralia V.; Song, Young-Cheol; Lee, Sam-Pin
Abstract: Water dropwort ( Oenanthe javanica DC) was co-fermented with Leuconostoc mesenteroides SM and Lactobacillus plantarum K154 to produce a novel functional food ingredient enriched with dextran and γ-aminobutyric acid (GABA). Dextran production was maximised with a water: dropwort ratio of 80: 20 (w/w) and 20% sucrose, reaching a consistency index of 6 Pa·s n after fermenting for 3 days at 25 °C. To achieve a successful second fermentation, L. plantarum K154 was cultured in the presence of 3% monosodium glutamate (MSG) and 0.25% yeast extract for 7 days, resulting in a pH of 4.14, 1.6% acidity, and a viable cell count of 8.04 log CFU/mL. Also, a yield of 10 mg/mL of GABA was achieved by the efficient bioconversion of the MSG substrate. In conclusion, fermented water dropwort as a functional food ingredient containing dextran, GABA, and probiotics was efficiently produced by consecutive co-fermentation using Leu. mesenteroides SM and L. plantarum K154. Highlights: A fermented water dropwort functional ingredient was produced. Two bacterial strains from kimchi were used for the co-fermentation. The co-fermented product was enriched with GABA, dextran, and probiotics. The co-fermentation produced more GABA than a single strain fermentation.